Self-certainty: parallels to attitude certainty - Richard E. Petty (International Journal of Psychology and Psychological Therapy, 2007)
The purpose of this article is to apply theory and research on attitude certainty to thestudy of the self. Our main goal is to show that research on attitudes, and in particularattitude certainty, can provide useful insights into self-related phenomena. By consideringresearch on attitudes, we may be able to re-interpret previous self-related findings, makenew predictions regarding the self, and increase the precision with which we can makeexisting predictions. Furthermore, this framework can offer new ideas for research onattitudes as well and foster integration between the areas. In this paper, we will 1) outlinesome fundamental parallels between attitudes and self research, 2) discuss the specificconstruct of self-certainty, including both the consequences and the origins of certainty,using research on attitude certainty as our organizing framework, and 3) suggest newideas that this analysis can produce